(untitled) (Research, Society and Development, 2025)
This article aims to discuss the appearance of the body between physical and mental aspects, through a narrative review of literature. Body appearance, can be presented under two trends in the search for a good well-being and self-esteem. On the one hand, it refers to a movement that focuses on excessive care with the good appearance of the body, being directly related to the feeling of well-being and self-esteem. This trend is more expressive, having historical roots, associated with consumerism that presents in the media an ideal of body to be achieved. On the other hand, it presents a movement that is less expressive and, which refers to the possibility of sustaining well-being and self-esteem, relativizing the need to always maintain a good self-image as a condition for well-being. Naturally accepting what cannot be changed without affecting self-esteem, seeking possibilities of self-realization, of raising self-esteem independent of and beyond the good image of the body. It is human nature to seek physical and mental well-being.